Perceived organizational support and organizational citizenship behavior–A study of the moderating effect of volunteer participation motivation, and cross-level effect of transformational leadership and organizational climate - Kao, Jui-Chung; Cho, Cheng-Chung; Kao, Rui-Hsin (Frontiers in Psychology, 2023)
The purpose of this study is to examine the relationship between perceived organizational support and organizational citizenship behavior, and to explore the moderating effect of volunteer participation motivation on the relationship between the variables, as well as the cross-level effect of transformational leadership and organizational climate. In this study, the front-liners of Taiwan’s National Immigration Agency were the study subjects. A total of 289 employee questionnaires were filled out and returned. It was found that employees’ POS had a positive effect on OCB, while volunteer participation motivation had a moderating effect on the relationships between the variables. Furthermore, transformational leadership and organizational climate were found to have a cross-level effect on enhancing employees’ POS, boosting their motivation to volunteer, and triggering more OCB in employees. The results of this study provide the organization with development measures to encourage its employees to convey more OCB, and improve their service performance. Moreover, based on research evidence that an organization encourages employees to actively participate in voluntary work, and should promote cooperation between the employees and the public by enhancing their sense of public responsibility, improving their services to the public, creating a harmonious work climate for the employees, and offering more opportunities for the public to engage with the employees.